Dancing shoes - Streatfeild, Noel. (New York : Random House, 2003)
After her mother's death, Rachel and her adopted sister Hilary are taken in by Aunt Cora, who runs a dancing school where Rachel's spoiled cousin Dulcie is the star pupil.
Book Links (A.L.A.).
School Library Journal.
5.0
5-8
Keywords: Behavior -- Fiction; Dance -- Fiction; Orphans -- Fiction; Dance -- Fiction; Human behavior -- Fiction; Orphans -- Fiction; England -- Fiction; England -- Fiction